2020
DOI: 10.3390/app10186240
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Redox Biomarkers in the Course of Caries and Periodontal Disease

Abstract: Caries are a pathological process of extracorporeal nature, characterized by demineralization of inorganic substances as well as proteolysis triggered by acids produced by bacteria present in dental plaque, as a result of metabolism of sugars of both external and internal origin. Periodontal disease, on the other hand, is a multifactorial degenerative disease associated with inflammation, involving a group of tissues that surround the dental cervix and root of the tooth. It is believed that one of the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 139 publications
0
8
0
Order By: Relevance
“…An extensive body of empirical data indicates that the MDA level in bodily fluids may be a reliable indicator of the extent of oxidative damage to cells in the body [5]. Available research indicates that MDA levels are increased due to cancer [6], atherosclerosis [7], diabetes [8], liver disease [9] and preeclampsia [10], as well as in smokers, while recent data suggest a strong link with periodontal disease [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive body of empirical data indicates that the MDA level in bodily fluids may be a reliable indicator of the extent of oxidative damage to cells in the body [5]. Available research indicates that MDA levels are increased due to cancer [6], atherosclerosis [7], diabetes [8], liver disease [9] and preeclampsia [10], as well as in smokers, while recent data suggest a strong link with periodontal disease [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Namely, in the course of periodontal disease, free radical production by polymorphonuclear leukocytes increases as a defense mechanism against periodontopathogens. Existing studies indicate that, in the course of periodontal disease, LPO products such as MDA are released and participate in the progress of periodontal tissue inflammation and destruction [13][14][15][16][17][18]. However, periodontal therapy is believed to induce a reduction in this marker.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid peroxidation triggered by free radicals results in changes in the structural and functional integrity of cell membranes. Several lipid peroxidation products such as malondialdehyde (MDA), 4-HNE, and isoprostane have been used to assess both local and systemic oxidative damage associated with periodontitis [ 27 , 28 ]. 4-HNE is a major aldehyde end product associated with lipid peroxidation, but data on this biomarker in periodontitis are limited for now.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters cannot highlight the beginning of the periodontitis process. For this reason, it is necessary to find predictable parameter variations to diagnose periodontal disease early [ 77 ]. Scientists are studying biomarkers that can be used for this goal.…”
Section: Studies Of Possible Biomarker For Periodontitismentioning
confidence: 99%
“…Wei et al [ 107 ] and Yang et al [ 111 ] showed an increase in SOD activity in patients with periodontitis compared with the control groups. Moreover, SOD is positively correlated with the CAL, bleeding on probing (BoP), probing depth (PD), gingival index (GI), and plaque index (PI) [ 77 ]. It was seen by Wei et al [ 107 ] and Novakovic et al [ 112 ] that after scaling and root planning the level of SOD diminishes and GPX reaches the concentration present in the control group.…”
Section: Studies Of Possible Biomarker For Periodontitismentioning
confidence: 99%